Worksheet MA 114 Spring 2013 1. Show that the curve with equation y = cosh 2x − 6 sinh x has a stationary point, and find its x-coordinate in logarithmic form. dy Solution: Find and where this derivative is 0. dx dy = 2 sinh(2x) − 6 cosh(x) dx 2 sinh(2x) − 6 cosh(x) = 0 e2x − e−2x ex + e−x =3 2 2 e2x − e−2x =3 ex + e−x ex − e−x = 3 (ex )2 − 3ex − 1 = 0 √ 9+4 e = √2 3+ 9+4 = 2 √ 3+ 9+4 x = ln 2 x 3± (Because ln must take a positive argument.) 2. Find the exact solution to 3 cosh x = 4 sinh x, giving the answer in terms of a logarithm. Solution: 3 cosh(x) = 4 sinh(x) 3ex + 3e−x = 4ex − 4e−x ex − 7e−x = 0 (ex )2 − 7 = 0 √ ex = 7 1 x = ln 7 2 3. Find the equation of the tangent to the curve y = cosh(2x) at x = 1. dy Solution: = 2 sinh(2x). Set x = 1 and m = y 0 (1) = 2 sinh 2, so the equation of the dx tangent line is y − cosh 2 = 2 sinh 2(x − 1). MA 114 Worksheet Spring 2013 4. Find the equation of the tangent to the curve y = sinh(x) + cosh(x) at x = 0. dy = cosh x + sinh x. Set x = 0 and m = y 0 (0) = cosh 0 + sinh 0 = 1, so the Solution: dx equation of the tangent line is y − 1 = 1(x − 0), or y = x + 1. 5. Suppose we know that the hyperbolic cosine of a certain variable is equal to 1. What is the hyperbolic cosine of twice that variable? Solution: We are given that cosh a = 1. We must find cosh(2a). Method 1: There is only one value of a that will make cosh a = 1 and that is a = 0. Then 2a = 0 and cosh(2a) = 1. Method 2: Since cosh2 a − sinh2 a = 1 and cosh a = 1, we see that sinh2 a = 0 and thus sinh a = 0. Then cosh(2a) = cosh2 a + sinh2 a = 1 + 0 = 1. 6. How is the hyperbolic secant of 10 related to the hyperbolic secant of −10? Solution: Since cosh x is an even function, it follows that sech x = 1/ cosh x is also even. Thus, sech(−10) = sech(10). 7. Using the definitions of the hyperbolic functions, show that 2 cosh2 x − cosh 2x = 1. Solution: Method 1: Using hyperbolic trig identities: 2 cosh2 x − cosh 2x = 2 cosh2 x − (cosh2 x + sinh2 x) = cosh2 x − sinh2 x =1 Method 2 2 e2x + e−2x ex + e−x − 2 cosh x − cosh 2x = 2 2 2 2x −2x e +2+e e2x + e−2x =2 − 4 2 2·2 = 4 =1 2 Page 2 of 7 MA 114 8. Find Worksheet Spring 2013 d coth (e2tx ). Solution: dt d coth e2tx = −csch2 e2tx e2tx (2x) dt = −2xe2tx csch2 e2tx 9. R cosh(3x) dx Z cosh(3x) dx = 10. R 1 sinh(3x) + C. 3 sinh(x + 1) dx Z sinh(x + 1) dx = cosh(x + 1) + C. 11. R sinh3 x cosh6 x dx Solution: Just like regular trig functions, rewrite sinh3 x = sinh x sinh2 x = sinh x(cosh2 x− 1), and then integrate. Z 3 Z 6 sinh x cosh x dx = = 12. R sinh x(cosh2 x − 1) cosh6 x dx 1 1 cosh9 x − cosh7 x + C 9 7 sinh2 x cosh2 x dx 1 Solution: To really simplify matters, rewrite sinh2 x = (1 + cosh(2x)) and cosh2 x = 2 1 (1 − cosh(2x)). 2 Z 2 2 Z 1 1 (1 + cosh(2x)) (1 − cosh(2x)) dx 2 2 Z 1 =− (1 − cosh2 (2x)) dx 4 Z 1 1 =− 1 − (1 + cosh(4x)) dx 4 2 Z 1 = (−1 + cosh(4x)) dx 8 1 1 −x + sinh(4x) + C = 8 4 x 1 =− + sinh(4x) + C 8 32 sinh x cosh x dx = Page 3 of 7 MA 114 Worksheet Spring 2013 d 13. Define the gudermannian function by gd(x) = tan−1 (sinh x). Show that gd(x) = dx sech x. Solution: We differentiate. d d (gd(x)) = tan−1 (sinh x) dx dx cosh x = 1 + sinh2 x cosh x = cosh2 x 1 = cosh x = sech x π . Prove that gd(x) = f (x) by showing that they have the 2 same derivative and that f (0) = gd(0). 14. Let f (x) = 2 tan−1 (ex ) − Solution: We differentiate. π d 2ex 2 tan−1 (ex ) − = dx 2 1 + e2x 2ex e−x = 1 + e2x e−x 2 = x e + e−x 1 = cosh x = sech x d = (gd(x)) dx Thus, since the functions have the same derivative, they must differ only by a constant, π i.e., gd(x) + C = 2 tan−1 (ex ) − . By comparing the two functions at x = 0 we can find 2 Page 4 of 7 MA 114 Worksheet Spring 2013 the value of this constant. π gd(0) + C = 2 tan−1 (e0 ) − 2 π tan−1 (sinh 0) + C = 2 tan−1 (1) − π π 2 −1 tan (0) + C = 2 − 4 2 π π 0+C = − 2 2 C=0 Thus, the two functions are equal. 15. Show that i. cosh(x) = sec(gd(x)). sec(gd(x)) = sec tan−1 (sinh x) q 1 + sinh2 (x) = 1 q = cosh2 (x) = cosh x ii. tanh(x) = sin(gd(x)). sin(gd(x)) = sin tan−1 (sinh x) sinh x =q 1 + sinh2 (x) sinh x cosh(x) = tanh x = iii. coth(x) = csc(gd(x)). csc(gd(x)) = csc tan−1 (sinh x) q 1 + sinh2 (x) = q sinh x cosh2 (x) = sinh x cosh x = sinh x = coth x Page 5 of 7 MA 114 Worksheet Spring 2013 iv. sech(x) = cos(gd(x)). cos(gd(x)) = cos tan−1 (sinh x) 1 =q 1 + sinh2 (x) 1 =q cosh2 (x) 1 cosh x = sech x = v. csch(x) = cot(gd(x)). cot(gd(x)) = cot tan−1 (sinh x) 1 = sinh(x) = csch x 16. Find i. d ln(cosh x))5 dx 4 1 d ln(cosh x))5 = 5 ln(cosh x) sinh x dx cosh x 4 = 5 tanh(x) ln(cosh x) ii. d sinh(ln x) dx 1 1 sinh(ln x) = x− 2 x d 1 1 sinh(ln x) = 1+ 2 dx 2 x iii. iv. d tanh x e dx d tanh(ex ) dx d tanh x e = sech2 x · etanh x dx d tanh(ex ) = ex sech2 (ex ) dx Page 6 of 7 MA 114 v. Worksheet Spring 2013 d sinh(cosh3 x) dx d sinh(cosh3 x) = cosh cosh3 x 3 cosh2 x sinh x dx 17. Show that (cosh(x) + sinh(x))n = cosh(nx) + sinh(nx) for any integer n. Solution: ex + e−x ex − e−x (cosh(x) + sinh(x)) = + 2 2 x n 2e = 2 nx =e n n Likewise: enx + e−nx enx − e−nx + cosh(nx) + sinh(nx) = 2 2 nx 2e = 2 nx =e Thus, clearly (cosh(x) + sinh(x))n = cosh(nx) + sinh(nx) for any integer n. 18. At what point on the curve y = cosh x does the tangent have slope 1? d Solution: We need to find the value of x so that cosh x = 1. dx d cosh x = sinh x dx sinh x = 1 x e − ex =1 2 ex − ex = 2 (ex )2 − 2ex − 1 = 0 √ √ 2± 8 e = =1± 2 2 x Thus, x = ln 1 + √ 2 . Page 7 of 7